Performance degradation and mitigation strategies of silver nanowire networks: a review. Issue 3 (4th May 2022) - Guan, Peiyuan; Zhu, Renbo; Zhu, Yanzhe; Chen, Fandi; Wan, Tao; Xu, Zhemi; Joshi, Rakesh; Han, Zhaojun; Hu, Long; Wu, Tom; Lu, Yuerui; Chu, Dewei
Abstract: In view of the drawbacks of high-cost and inherent brittleness of indium tin oxide (ITO) based transparent electrodes, silver nanowires (AgNW) networks have been considered as promising alternatives owing to their excellent optical transparency, mechanical flexibility, and compatibility with large scale printing process. AgNWs have been applied as transparent electrodes in many electronic devices, however, in many cases, they inevitably interact with the surrounding media (e.g., temperature, electric field, UV light irradiation, etc.) which will cause performance degradation. For instance, AgNWs show a typical Rayleigh instability phenomenon when the external temperature is higher than a critical point. Moreover, a specific range of UV light or/and intensive current density can accelerate the partial breakage of AgNW networks. To develop highly stable AgNW based transparent electrodes for flexible electronic devices, intensive research works have been conducted to mitigate the degeneration issues. In this review, the degradation mechanisms of AgNW based transparent electrodes have been systematically studied. Furthermore, the mainstream strategies for mitigating the deterioration of AgNW based transparent electrodes have been analyzed. Finally, the present challenges in current materials processing, and future research directions have been discussed.